Simultaneous removal of heavy metals from synthetic storm water using sustainable urban drainage systems. Issue 6 (3rd July 2019) - Allabashi, Roza; Haile, Tadele Measho; Fuerhacker, Maria; Pitha, Ulrike; Scharf, Bernhard; Stach, Wolfgang; Ziegenbalg, Falko; Heidinger, Sandra; Ertl, Thomas
ABSTRACT: Utilization of filtration systems plays a significant role in removing contaminants from storm water runoff. In this study, pilot-scale experiments are conducted to investigate heavy metal removal capacity for ten substrate mixtures. Tested filter substrates contained 10−15 vol.-% compost. The experiments are conducted using synthetic storm water and heavy metal loads of 4–12 months based on a ratio 7:1 between connected drainage area and filter area. All filter substrates performed similarly in removing Cr, Cu, Pb and Zn, while the behaviour with Ni was somewhat different. The removal efficiency was more than 80% for Cr, Cu, Pb and Zn, compared to 53% to 88% for Ni. Regardless of substrate composition, the removal efficiency decreased in the following order: Pb Zn > Cr > Cu > Ni. Measured effluent concentrations for Pb, Cr and Cu were very low and met the Austrian Groundwater Quality Ordinance requirements.